Thermal stresses associated with a thermosensitive multilayered disc analysed due to point heating - Srinivas, V.B.; Manthena, V.R.; Warbhe, S.D.; Kedar, Ganesh D.; Lamba, Navneet Kumar (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, analytical solutions are presented for temperature and thermal behavior of a thermosensitive multilayered annular disc due to point heat source. Convective heating is applied to both the innermost and outermost layers. The nonlinearity of the thermal diffusivity equation is dealt using Kirchhoff`s transformation technique. A finite integral transform in the form of Bessel`s function is used to deal with the radial variable r. Fourier transform and angular eigen functions are also used to solve the thermal diffusivity equation. Deflection, resultant forces, shearing forces, resultant moments and thermal stresses are obtained. A mathematical representation is formulated for a 3-layered disc, with the inner, middle and outer layers composed of copper, zinc and aluminum respectively. The results are depicted graphically.
Keywords: multilayered annular disc; thermosensitive; heat conduction; instantaneous point heat source; deflection; stresses